ANALISIS PENGARUH DEBT TO TOTAL ASSET RATIO (DAR), DEBT TO EQUITY RATIO (DER), RETURN ON ASSET (ROA), DAN NET PROFIT MARGIN (NPM) TERHADAP DEVIDEND PAYOUT RASIO (DPR) PADA PERUSAHAAN OTOMOTIF YANG LISTING DI BURSA EFEK INDONESIA - Azizah Syarifahtul Nuraeni; Aliah Pratiwi (Jurnal Ilmiah Satyagraha, 2022)
The purpose of the study was to determine the efect of Debt to TotalAsset Ratio, Debt to Equity Ratio, Return On Asset, dan Net Profit Margin onDividend Payout Ratio. The object used in this study is the automotive subsectorliste on the indonesian stock exchange wit a sample of 4 companies selectedusing purposive sampling method. The data analysis technique used to process thedata in this research is the Classsical Assumption Test which consist of (1)Normality Test, (2) Multicollinearity Test, (3) Heteroscedasticity Test, and (4)Autocorrelation Test, Multiple Linear Reggression Analysis, CorrelationCoefficient and Determination, as well Partial Test (T Test) and SimultaneousTest (F Test). The result of this research is the Debt to Total Asset Ratio (DAR)has no effect on the Dividend Payout Ratio (DPR). Debt to Equity Ratio (DER) has a negative effect on the Dividend Payout Ratio (DPR). Return On Assets(ROA) Has No Effect on the Dividend Payout Ratio (DPR). And the Net ProfitMargin (NPM) has no effect on the Dividend Payout Ratio (DPR). Then the Debtto Total Asset Ratio (DAR), Debt to Equity Ratio (DER), Return On Assets (ROA),and Net Profit Margin (NPM) have no effect on the Dividend Payout Ratio (DPR).